School meals are evolving: Has the evidence kept up? - Alderman, Harold; Bundy, Donald; Gelli, Aulo (Oxford University Press, 2024)
School meal programs are popular social programs. They are provided to 61 percent of primary students in high-income countries but to a smaller share of students in less wealthy countries. There is a body of evidence documenting their contribution to education, health and nutrition, and social protection. But in each domain, program objectives have evolved: schooling is recognized to be more about learning than grades obtained; nutrition goals include healthy diets that reduce risks of non-communicable diseases and are more environmentally responsible; social protection programs aim to respond to acute crises and address chronic poverty. In addition to assisting in these sectors, school meal programs are tasked with creating food systems that assist smallholder farmers, an endeavor that has yet to be extensively studied. This review examines the latest evidence on these evolving dimensions of school meal programs. Findings suggest that while there is a strong evidence base for school meals, there are also specific gaps in the evidence of effectiveness and a particular lack of clarity around costs. The country-led School Meals Coalition, developed in response to COVID pandemic-related school closures, has brought new momentum to national programs and new urgency for reliable evidence on effectiveness and costs.